2014
DOI: 10.3846/16111699.2012.707984
|View full text |Cite
|
Sign up to set email alerts
|

An Approach to Multiple Attribute Decision Making Based on the Induced Choquet Integral With Fuzzy Number Intuitionistic Fuzzy Information

Abstract: Abstract. In this paper, we investigate the multiple attribute decision making problems with fuzzy number intuitionistic fuzzy information. Firstly, some operational laws of fuzzy number intuitionistic fuzzy values, score function and accuracy function of fuzzy number intuitionistic fuzzy values are introduced. Then, we have developed two fuzzy number intuitionistic fuzzy Choquet integral aggregation operators: induced fuzzy number intuitionistic fuzzy choquet ordered averaging (IFNIFCOA) operator and induced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(15 citation statements)
references
References 29 publications
(24 reference statements)
0
15
0
Order By: Relevance
“…Note that researchers can extend the UAO operator by adding some other key concepts like distance measures (Zeng, Merigó, & Su, 2013), fuzzy systems (Zeng, Su, & Le, 2012), power aggregations (Wei, Zhao, Wang, & Lin, 2013), Choquet integrals (Belles, Merigó, Guillen, & Santolino, 2014;Wei, Lin, Zhao, & Wang, 2014) and generalized multiple aggregations (Zhou, Chen, & Liu, 2013).…”
Section: Aggregation Systemsmentioning
confidence: 99%
“…Note that researchers can extend the UAO operator by adding some other key concepts like distance measures (Zeng, Merigó, & Su, 2013), fuzzy systems (Zeng, Su, & Le, 2012), power aggregations (Wei, Zhao, Wang, & Lin, 2013), Choquet integrals (Belles, Merigó, Guillen, & Santolino, 2014;Wei, Lin, Zhao, & Wang, 2014) and generalized multiple aggregations (Zhou, Chen, & Liu, 2013).…”
Section: Aggregation Systemsmentioning
confidence: 99%
“…Finally, a practical example for evaluating the psycholinguistic teaching effect is given to verify the developed approach. In our future studies, our results may be further extended by using the traditional uncertain and fuzzy decision making theories and techniques [34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49].…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, it has been developed aggregation operators in combination with OWA operator and other instruments. Merigó (2009) Gil-Lafuente and Merigó (2007) Merigó and Gil-Lafuente (2006, 2008a, 2008b, 2008c suggested distance and index selection for OWA operators, Wei (2009) developed an induced linguistic hybrid geometric aggregation of OWA operators, Zhao et al (2010) proposed OWA operators for intuitionistic fuzzy sets, Zhou and Chen (2010) worked in logarithm aggregation in OWA operators, Peng and Ye (2014) introduced the induced uncertain pure linguistic hybrid harmonic averaging operator, Xu et al (2014) proposed intuitionistic fuzzy Einstein Choquet integral operators, Zhou et al (2014) suggested intuitionistic fuzzy weighted cosine similarity measure, He et al (2014) introduced an intuitionistic fuzzy geometric, Wei et al (2014) worked on multiple attribute decision making, suggested non-homogenous preferences information, He et al (2015a) proposed intuitionistic fuzzy information, He et al (2015b) introduced fuzzy interaction Bonferroni, He et al (2015c) suggested hesitant fuzzy power Bonferroni. All these operators offer multiple techniques that can be used to solve decision-making problems.…”
Section: Decision Making With the Ordered Weighted Averaging (Owa) Opmentioning
confidence: 99%